PERANCANGAN TYPEFACE DENGAN PENDEKATAN KARAKTER AKSARA LONTARA’ PADA HURUF LATIN - Andi Ihsan Said Safi (Saraswati)
The typeface is one of the integral design element in visual communication. Various varieties and forms of the typeface is now easier for designers to choose how he wanted the visual style typeface. To examine the script character shapes Lontara 'in the application and design of visual communication through the viewpoint of the theory of modern typography guidelines and the creation of a new font style as treasury culture in Indonesia.Typografi experimental approach to explore the form of letters to the alphabet character Lontara 'to be achieved with the technique 5W + 1H and measures undertaken such as observation, study of literature, data analysis and study of visual form. a typeface in the form of a series of works Uppercase letters, numerals and punctuation. It is expected that the creation of the typeface Lontara 'This adds to our love towards our own culture. The role of the letter is very important for the human need to communicate visually, not only represents the world of communication, but also the aesthetic tervisual art in any media that could dihampirinya, so that in this limit development efforts must be done, particularly in context of the development of the local characters who turn out to have a very beautiful aesthetic side of diverse forms. Keywords: culture, script, Indonesia, Experimental typography